Principles of Entrepreneurship (ENT530): Social Media Portfolio: De’Rolls / Siti Aishah M.A.Karim - M.A.Karim, Siti Aishah (2021)
The report is about how student using social media platform to promote their product. Student was required to create their own Facebook page in order to complete this social media portfolio assignment. For this project the product that I choose was Flavored Spring Roll snacks and promote it using the Facebook page that I had created which is De’Rolls. De’Rolls have been liked by 163 people and followed by 166 followers. The introduction of our product in term of our address, organizational chart, description of the product and price list will be explained further in the introduction part. This assignment has taught student practically on how they manage social media to interact with buyer and grab more consumer through this platform. As we know, Social media are network application that enables you to engage with others, publish and produce content, and interact with others through online communities. The usage of social media platform nowadays has been a trend for seller in order to promote and introduce their product in the market. With the number of online sellers that keep increasing over the years, therefore as an online seller we need to build our own strategy regarding our content and posting on our social media as there are more competition exist when we sell our product on social media platform. Thus, this report focuses on how student use hard sell, soft sell and teaser as their posting method and promote their product. A hard sell is a selling or branding strategies that uses exceptionally direct and demanding language. A hard sell is intended to persuade a buyer to buy a product or service right away, rather than considering his or her options and possibly deferring the purchase. While soft sell was a sales and promotional efforts that use gentle language and a non-aggressive strategy. A soft sell is intended to avoid enraged potential clients and drive them away. Soft selling, may not result in a sale the first time a product is given, but it does help to stimulate repeat sales as it was a persuading and delicate sales method to attract buyers. In the meanwhile, a teaser posting was a content to create excitement from consumers to know more about our product. With a creative content and great editing, a teaser post can help sellers in order to grab people attention to know more about their product. There are 16 soft sells, 16 hard sells and 7 teaser that required to accomplished this assignment. Variety of posting had been done by me to attract consumer to buy my flavored spring rolls snacks.